Proposal for the development of a teaching guide for guided tours for children at the Museum of Pre-Columbian Gold of Costa Rica - Arguedas Abarca, María Fernanda (2026)
This article presents a proposal for the development of a Teaching Guide for guided tours for children in 4th, 5th, and 6th grade of Basic General Education (9-12 years old) at the Museum of Pre-Columbian Gold of Costa Rica. The research, with a qualitative approach, combined documentary review, non-participant observation, and interviews with students, teachers, museum guides, and specialists in the field. The main result was the development of a Teaching Resources Guide that organizes devices, activities, and teaching strategies adapted to the age, interests, and prior knowledge of visitors, promoting active participation during the various dynamics. The main conclusions highlight that the guide not only strengthens educational mediation and facilitates interaction between guides and students, but also contributes to a reflection on how historical and cultural knowledge is transmitted to children, fostering an appreciation of heritage, and cultural thinking.